Cover Image. Issue 9 (9th May 2019) - Costentin, Guillaume; Derrey, Stéphane; Gérardin, Emmanuel; Cruypeninck, Yohann; Pressat‐Laffouilhere, Thibaut; Anouar, Youssef; Wallon, David; Le Goff, Floriane; Welter, Marie‐Laure; Maltête, David
Abstract : COVER ILLUSTRATION 3D reconstruction and axial slices of one subject's brain in MNI 152 space. Tracts involved in verbal fluency which are disrupted along the trajectories of electrodes implanted for subthalamic deep brain stimulation in Parkinson's disease are represented. Blue on 3D reconstruction : Superior Longitudinal Tract, orange : Inferior Longitudinal Tract, green : Arcuate Fasciculus, light blue on axial slice : Anterior Thalamic Radiation and violet : Fronto‐striatal Tract.